AN EMPIRICAL STUDY OF THE RELATIONSHIP BETWEEN STOCK MISPRICING AND INVESTMENTS: EVIDENCE FROM LONDON STOCK EXCHANGE - Mei, Chen (2014)
This dissertation investigates the impact of the stock market mispricing on corporate investment decisions for the UK stock market over the period from 1994 to 2012. In order to analyze this effect thoroughly, the market to book ratio is decomposed into firm level mispricing, industry level mispricing and growth opportunities components. The results of the dissertation show that only the growth component determines the investment decisions while holding the financial slack factors constant. Inconsistent with my predictions, neither the firm level mispricing nor the industry level mispricing has minimal power in explaining the changes in corporate investments. This might be due to the unique characteristics of chosen stock market and period.